2000
DOI: 10.4049/jimmunol.164.6.3102
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of GM-CSF Expression Plasmid Administration Influences the Th1/Th2 Response Induced by an HIV-1-Specific DNA Vaccine

Abstract: The mechanism of immune activation induced by a plasmid-encoding GM-CSF (pGM-CSF), administered in combination with a DNA vaccine encoding the envelope of HIV, was studied. Injecting pGM-CSF i.m. into mice 3 days before DNA vaccination primarily induced a Th2 response. Simultaneous administration of the DNA vaccine plus pGM-CSF activated both a Th1 and a Th2 response. When the plasmid was injected 3 days after DNA vaccination, enhancement of Th1 immunity predominated. These results suggest that the timing of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 57 publications
9
78
1
1
Order By: Relevance
“…GM-CSF administration before target gene inoculation polarized the response to a Th2 type, whereas a Th1 type response could be induced when GM-CSF was administered after target gene inoculation. 19 Thus, GM-CSF may be a neutral cytokine that serves as an amplifier for either a Th1 or a Th2 response depending on the context and the timing of DNA vaccine. GM-CSF could amplify Th1 or Th2 immune responses depending on different strains of mice used in the various studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GM-CSF administration before target gene inoculation polarized the response to a Th2 type, whereas a Th1 type response could be induced when GM-CSF was administered after target gene inoculation. 19 Thus, GM-CSF may be a neutral cytokine that serves as an amplifier for either a Th1 or a Th2 response depending on the context and the timing of DNA vaccine. GM-CSF could amplify Th1 or Th2 immune responses depending on different strains of mice used in the various studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pulendran et al found that polarized Th1 type immune responses were induced by GM-CSF via either cell vaccine or DNA immunization. [16][17][18] Okada et al 13 demonstrated that the Th2 immune responses were induced by intranasal vaccine, 13 and Kusakabe et al 19 found that Th2 immune responses were induced by injection of a GM-CSF plasmid before the injection of plasmid containing the target antigens.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Although immunization with engineered tumor cells secreting low levels of GM-CSF generated measurable increases in antitumor effect, highdose expression of GM-CSF instead impaired the immune responses by inducing the recruitment of myeloid-derived suppressor cells. 34 GM-CSF may also promote tumor cell transmigration through the endothelial barrier 35 and high levels of GM-CSF secreted by cancer cells were shown to promote osteolytic bone metastasis.…”
Section: Non-human Primate Study Against Human Her-2/neu H-j Ko Et Almentioning
confidence: 99%
“…30 The amino acid sequence of hTERT was analyzed for the 8-10 amino-acid peptide binding sequences for H-2K d using two computer programs, BIMAS and SYFPEITHI. 31 The COOH-terminal end of hTERT (cTERT code for amino acids 795-1132) contains peptide sequences found to have higher scores by the programs.…”
Section: Tert Expression Vector For Immunizationmentioning
confidence: 99%
“…IgG2a are associated with predominantly T-helper 1 (TH1) responses. 22,31 The CCL21/cTERT vaccine induced significantly higher IgG2a (Po0.0005) titers compared to the cTERT alone vaccine both in the prophylactic and the therapeutic vaccine models (Table 1). Both the cTERT alone vaccine and CCL21 alone failed to induce strong IgG2a responses.…”
Section: Induction Of Humoral Immune Response Against Ctertmentioning
confidence: 99%